Research on the modeling of the Internet delay space - Zhan-feng WANG; Ming CHEN; Chang-you XING; Bing LI; Xiao-feng QIU (Tongxin xuebao)
Firstly,the concept of the modeling of the Internet delay space was presented,and then various delay models were analyzed from the evolvement view.In the following section,the challenges of Internet delay space modeling were pointed out.Finally,the future trends of the modeling of the Internet delay space were discussed.